Using Riddle Game in Increasing Vocabulary of the Eighth Grade Students - Elis Susanti; Muhammad Arid; Andi Patmasari; Hastini Hastini (MASI Mandiri Edukasi, 2026)
This study aims to examine whether the Riddle Game can increase the vocabulary of eighth-grade students at SMP Negeri 19 Palu. This research was conducted because it was discovered that students fear making mistakes and have difficulty understanding meaning, using words, and spelling them. Students feel bored when learning from textbooks and only listening to the teacher's explanations. The research used a quasi-experimental design with two groups. The population was 103 students from 4 classes at SMP Negeri 19 Palu. The sample comprised two classes: class VIII A as the experimental group and class VIII B as the control group. Vocabulary tests consisting of multiple-choice, categorization, spelling words, and sentence correction items were used as instruments for both pre-test and post-test. Data analysis used the Mann-Whitney U test to test differences between groups and the Wilcoxon Signed-Rank test to determine changes within each group. The results show that the experimental group achieved a higher post-test mean score, from (32.72) to (72.76), compared to the control group with a score from (36.42) to (47.38), with a significant difference between both groups (p < 0.05). These findings indicate that the Riddle Game significantly increases eighth-grade students' vocabulary at SMP Negeri 19 Palu.